Strategies to achieve adherence to prone positioning in awake COVID-19 patients with highflow nasal oxygen. A case series - Marina Busico; Mariela Marisol Laiz; José García Urrutia; Maria Emilia Amado; Darío Villalba; Santiago Nicolás Saavedra; Adrián Gallardo; Arnaud W Thille (Canadian Journal of Respiratory Therapy, 2022)
Introduction: The use of high-flow nasal oxygen (HFNO) is a simple method that can reduce intubation in patients with hypoxemic acute respiratory failure (ARF). Early and prolonged prone position has demonstrated benefits on mortality in mechanically ventilated patients and on intubation in awake patients with ARF. However, strategies to achieve adherence to awake prone positioning (APP) have not been previously described. Case and outcomes: We present six patients with ARF due to COVID-19 treated with HFNO and APP. The median (p25–75) of PaFiO2 upon admission was 121 (112–175). The average duration of APP on the first day was 16 h (SD 5 h). Duration (median p25–75) in APP for the following 20 days was 13 (10–18) h/day. Several strategies such as the presence of a health care team, recreational activities, adaptation of the circadian rhythm, oral nutritional support, and analgesics were used to improve prone tolerance. None of the patients suffered from delirium, all were ambulating on discharge from the ICU and none require intubation. Conclusion: The case series presented show the feasibility of prolonged use of HFNO and APP in patients with COVID-19 and severe persistent hypoxemia and described strategies to enhance adherence.